EFEKTIVITAS PENERTIBAN PAJAK KENDARAAN BERMOTOR SECARA TERPADU DI PROVINSI RIAU - Thessya Ramadani; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Integrated motor vehicle tax control in Riau Province is a trrobosan that is made by the Riau Provincial Revenue Agency which aims to increase motor vehicle tax revenues in Riau Province. With the presence of the application of this control it is expected to increase public awareness of the importance of paying taxes on timelyly. The purpose of this study was to find out how effective in the control of motor vehicle tax that had been running and knew what the inhibiting and supporting factors were. This study uses an interactive analysis technique with a type of qualitative research using a descriptive approach and data on both primary and secondary data which is obtained through observation, interviews, and documentation then in analysis based on research problems. The results of this study show that the effectiveness of motorized vehicle tax turbanes is integrated in Riau Province in the receipt of motor vehicle tax has been said to be effective and run optimally. Supporting factors The effectiveness of motor vehicle tax control is human resources and facilities and infrastructure. Inhibitory factors are lack of participation and public awareness of taxpayers in paying motor vehicle tax.  Keywords: effectiveness, motor vehicle tax